2023
DOI: 10.1039/d3fo00009e
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of a sulfated polysaccharide from Gracilariopsis lemaneiformis and its potentiation of cisplatin antitumor activity in Colon-26 carcinoma tumor-bearing mice by inducing ferroptosis

Abstract: Ferroptosis, a form of regulated cell death caused by iron-mediated lipid peroxidation, has become a potential strategy to overcome drug resistance and improve the efficacy of traditional cancer treatments. In...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Our previous study illustrated that GP90 is a sulfate-rich polysaccharide that is composed mainly of (1→3)-linked 4-O-sulfate-⊎-D-galactose and (1→4)-linked 3,6-anhydro-⊍-L-galactose with a molecular weight of 12.45 kDa. 13 Previous studies have demonstrated that sulfate groups can serve as electrophilic groups, thereby augmenting the activity of GP. The activity of GP is intricately linked to the position and quantity of sulfate groups present on the polysaccharide backbone.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our previous study illustrated that GP90 is a sulfate-rich polysaccharide that is composed mainly of (1→3)-linked 4-O-sulfate-⊎-D-galactose and (1→4)-linked 3,6-anhydro-⊍-L-galactose with a molecular weight of 12.45 kDa. 13 Previous studies have demonstrated that sulfate groups can serve as electrophilic groups, thereby augmenting the activity of GP. The activity of GP is intricately linked to the position and quantity of sulfate groups present on the polysaccharide backbone.…”
Section: Resultsmentioning
confidence: 99%
“…12 In our previous investigation, it was observed that GP90, a sulfated polysaccharide derived from G. lemaneiformis, has the potential to reduce tumor growth in colon-26 carcinoma tumorbearing mice and enhance sensitivity to cisplatin. 13 These findings suggest that GP90 could have a positive impact on cisplatin therapy efficacy. Therefore, the present study aimed to explore the protective effects of GP90 on systemic inflammation and intestinal barrier damage caused by cisplatin treatment in C26 tumor-bearing mice.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Red ginseng polysaccharide (RGP) inhibited the proliferation of A549 and MDA‐MB‐231 cells by reducing the expression of GPX4, whereas ferrostatin‐1 counteracted the effects of RGP, suggesting that this polysaccharide could inhibit tumor development by regulating ferroptosis (Zhai et al, 2022). Cai et al isolated a new polysaccharide GP90 from Gracilariopsis lemaneiformis , which was composed of galactose and anhydro‐galactose (B. Cai, Luo, et al, 2023). Importantly, this polysaccharide promoted ferroptosis in C26 cells through the down‐regulation of SLC7A11 and GPX4, thus significantly attenuating cisplatin resistance in CRC.…”
Section: Regulation Of Ferroptosis By Natural Productsmentioning
confidence: 99%